2020
DOI: 10.1007/978-3-030-62807-9_59
|View full text |Cite
|
Sign up to set email alerts
|

Towards AR/VR Maturity Model Adapted to the Building Information Modeling

Abstract: The challenge of improving the efficiency of the different phases of a building or infrastructure life demands considerations of innovative technologies such as Augmented Reality (AR) and Virtual Reality (VR). During this last decade, AR/VR systems for construction started to be emerged. These applications aim to virtualize or augment in real time the content of the Building Information Modeling (BIM) in order to support continuous improvement. To ensure the maturity of these applications, implementing a matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 36 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Cluster 1 VR exemplifies the ongoing investigations within the domain of VR for virtual construction. This is typically achieved through 3D real-time computer graphics and advanced display devices, such as head-mounted displays (HMDs) [43]; leveraging VR facilitates with generation of comprehensive virtual construction environments, permitting users to partake in real-time interactions with digital entities [44], which enables project teams to effortlessly conceptualise and visualise their work content, thereby assisting them in making optimal decisions for construction projects [45,46]. Consequently, VR technology is currently employed in BIM to tackle a range of challenges to design, construction, and operation, encompassing design coordination, project planning, construction education, construction operation collaboration, and facility management [8,[47][48][49][50][51][52].…”
Section: Abstract Co-occurrence Analysismentioning
confidence: 99%
“…Cluster 1 VR exemplifies the ongoing investigations within the domain of VR for virtual construction. This is typically achieved through 3D real-time computer graphics and advanced display devices, such as head-mounted displays (HMDs) [43]; leveraging VR facilitates with generation of comprehensive virtual construction environments, permitting users to partake in real-time interactions with digital entities [44], which enables project teams to effortlessly conceptualise and visualise their work content, thereby assisting them in making optimal decisions for construction projects [45,46]. Consequently, VR technology is currently employed in BIM to tackle a range of challenges to design, construction, and operation, encompassing design coordination, project planning, construction education, construction operation collaboration, and facility management [8,[47][48][49][50][51][52].…”
Section: Abstract Co-occurrence Analysismentioning
confidence: 99%
“…A maturity model is a tool used to measure a project's maturity level according to key process indicators (KPIs) [17]. It provides a framework for evaluating an organization's capabilities in different areas such as strategy, process, and technology, as explained by Succar and Kassem [51].…”
Section: B Rq 2 What Are the Key Concepts Of Maturity Evaluation?mentioning
confidence: 99%
“…Currently, there are only two research studies available on the subject, as shown in Table 11. The first study is conducted by Assila et al [17] who proposed an advanced approach to developing a maturity model for BIM-based AR/VR evaluation. They defined three maturity levels based on a mapping between existing BIM and AR/VR maturity models.…”
Section: Student Engaging In the Studied Office To Analyze Business P...mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent time, tremendous advancements have been recorded in the in the field of internet and wireless communication, it appears that innovative applications are constructing the underlying foundation and basic framework infrastructure. This provides a solid ground for human life's day-to-day necessities [18][19][20][21][22] . Buildings are being created in such a way that they provide maximum comfort and ease to the inhabitants while using the least amount of energy possible in this period, where energy management is a major issue for everyone [23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%